Action Real-Time Strategy Gaming Experience Related to Increased Attentional Resources: An Attentional Blink Study - Gan, Xianyang; Yao, Yutong; Liu, Hui; Zong, Xin; Cui, Ruifang; Qiu, Nan; Xie, Jiaxin; Jiang, Dong; Ying, Shaofei; Tang, Xingfeng; Dong, Li; Gong, Diankun; et al. (Frontiers in Human Neuroscience, 2020)
Action real-time strategy gaming (ARSG) is a cognitively demanding task which requires attention, sensorimotor skills, team cooperation and strategy-making abilities. A recent study found that ARSG experts had superior visual selective attention (VSA) for detecting the location of a moving object that could appear in one of 24 different peripheral locations(Qiu et al., 2018), suggesting that ARSG experience is related to improvements in the spatial component of VSA. However, the influence of ARSG experience on the temporal component of VSA – the detection of an item among a sequence of items presented consecutively and quickly at a single location – still remains understudied. Using behavioral and electrophysiological measures, this study examined whether ARSG experts had superior temporal VSA performance compared to non-experts in an attentional blink (AB) task, which is typically used to examine temporal VSA. We predicted that ARSG experts should exhibit superior performance to non-experts in the AB task. Results showed that the experts outperformed the non-experts in their detection rates of targets. Furthermore, compared to the non-experts, the experts had faster information processing as indicated by earlier P3 peak latencies in an AB period, more attentional resources distributed to targets as indicated by stronger P3 amplitudes, and a more flexible deployment of attentional resources. These findings suggest that experts were less prone to the AB effect. Thus, long-term ARSG experience is related to improvements in temporal VSA. The current findings support the benefit of video gaming experience on the development of VSA.